Spent ground coffee – awaking the sustainability prospects - Kueh, Ahmad Beng Hong (Environmental and Toxicology Management, 2021)
This paper outlines the threat of spent coffee ground (SCG) towards environmental health and some promising remedial efforts carried out by the scientific community working against it. To maintain human and earth wellbeing, massive biowastes left behind by the rising popularity of coffee drinking and its processing must be properly addressed. The recent waste to wealth value engineering efforts carried out to repurpose these biowastes are first presented. Some promising applications of SCGs in various prospective civil engineering areas alongside their favorable findings are then summarized. Attributed to beneficial properties as reported in existing studies, silica fume is recommended as the potential constituent to mix with SCG for future construction materials exploration in overcoming both the biowaste and industrial waste issues.